Constructing Sustainable Maternal and Child Health Strategies: Analyzing Factors Associated with Low-Birth-Weight Incidence in Indonesia - Sari, Gita Nirmala; Sari, Dewi Nirmala; Fratidhina, Yudhia; Mulyati, Sri (Nurse Media Journal of Nursing, 2025)
Background: Maternal and child health (MCH) is crucial for public health, especially in low- and middle-income countries like Indonesia. Despite improvements in healthcare infrastructure, challenges remain in reducing maternal and neonatal mortality rates, with low birth weight (LBW) posing a significant concern. Previous research has largely examined individual factors, such as maternal age, parity, or nutritional status, in isolation. To date, there has been no comprehensive analysis integrating the various determinants of LBW within the Indonesian context.Purpose: This study aimed to comprehensively analyze factors associated with LBW incidence in Indonesia to inform sustainable MCH strategies.Methods: A cross-sectional study design was used to analyze data from 420 newborns and their mothers. A structured questionnaire and medical record reviews were used to collect data on maternal characteristics, antenatal care attendance, birth outcomes, and infant characteristics. Data were obtained from maternal and child health reports collected by primary health centers and hospitals under the Ministry of Health between 2021 and 2023. Statistical analyses, including bivariate Chi-square tests and multivariable logistic regression, were conducted to identify factors associated with LBW incidence.Results: The prevalence of LBW among newborns was 34.3%. Significant associations were found between LBW and maternal anemia (OR = 1.53; 95% CI = 1.16–2.03), irregular antenatal care attendance (OR 11.9; 95% CI 8.17–17.32), multiparity (OR = 0.61; 95% CI = 0.43–0.88), and preterm birth (OR = 11.22; 95% CI = 7.55–16.68). Primiparous mothers and full-term infants were less likely to experience LBW. Among the associated factors, irregular antenatal care visits and preterm birth emerged as the most dominant risk factors. No significant associations were observed with maternal complications, chronic diseases, infant gender, mode of delivery, or maternal age.Conclusion: Targeted interventions addressing maternal anemia, improving access to and adherence with antenatal care, and preventing preterm births are critical strategies for reducing LBW in Indonesia. The findings in this study underscore the need to improve maternal nutrition and encourage pregnant women to attend regular antenatal care visits.